PROCESSAMENTO E CARACTERIZAÇÃO DE AMOSTRAS SUPERCONDUTORAS UTILIZANDO O CONCENTRADO DE XENOTIMA - Silva, Simone Aparecida da (2007)
In this work, it was accomplished an experimental study about the substitution of the yttrium atom (Y) in the YBa2Cu3O7-x superconductor system for a rare earth oxide (RE2O3), gotten from the xenotime ore. Chemically, this substitution is possible due to the equality of the oxidation state between the Y3+ ions and the earth rare ions, which form the oxide. This way, this substitution should not modify the properties of the superconductor system significantly. The xenotime in its natural form is composed of a rare earth phosphate, zirconita and other heavy elements. The zirconita and the heavy elements can be separated by magnet or gravimetric process. The rare earth phosphate is chemically treated by the acid or the alkaline leaching process, resulting in a rare earth oxide (RE2O3). The xenotime ore used in this work was extracted from the Pitinga mine (AM, Brazil). Four polycrystalline samples were processed through the solid-state reaction, from the precursors: rare earth oxide (RE2O3), barium carbonate (BaCO3) and copper oxide (CuO), forming the REBa2Cu3O7-x superconducting oxide. The chracterization of the samples crystalline structures was studied by x-ray diffraction. The analysis of the samples superficial morphology was studied by optical microscopy and scanning electron microscopy (SEM). The properties of electronic transportation were analyzed by measurements of electric resistivity. Among the analyzed samples, one did not present null state of electric resistance. The measurements of electric resistivity for the other samples revealed superconductor behavior and showed that the critical temperature of the REBa2Cu3O7-x system is around 90 K, as in the YBa2Cu3O7-x system. Such values were confirmed by the measurement of magnetic susceptibility. The analyses of the Xray diffractograms of the samples revealed that the cell parameters of both systems are equal. These results indicate that the substitution of the Y for the rare earth oxide is possible, which may have important implications both from the point of view of basic research and the applied research.